The Effect Of Mung Beans On Pregnant Women With Chronic Energy Deficiency (CED) (HEALTH CARE: JURNAL KESEHATAN, 2025)
The prevalence of Chronic Energy Deficiency in pregnant women globally in 2016 was 30.1%. In Indonesia, it is estimated that 17.3% of pregnant women experience CED, and pregnant women with CED in West Sumatra province are around 16.5%. The occurrence of Chronic Energy Deficiency (CED) among pregnant women remains below the RENSTRA 2024 target, indicating that further efforts are necessary to enhance the nutritional status of expectant mothers. One effort to improve the nutrition of pregnant women with CED is to provide mung beans. The purpose of this research was to assess the impact of mung beans on pregnant women experiencing CED at BPM Erna Wena Padang Panjang. The type of research was pre-experimental with a group pretest-posttest design conducted from April to May 2025 at BPM Erna Wena Padang Panjang. The study population was all pregnant women with CED at BPM Erna Wena. The sample of this study was selected by purposive sampling of 16 pregnant women with CFD. The intervention was carried out by providing mung beans. The study results showed a change in the upper arm circumference of pregnant women after the intervention of 0.77 cm, with p-value = 0.001. There is an effect of giving mung beans to pregnant women with CED.